Tafsir Ayat ‘Tidak Ada Paksaan dalam Agama’ Perspektif Al Harari - Asyhari (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
The term 'religious freedom' is controversial among religious communities, particularly among Muslims. Both supporters and opponents within the Muslim community present arguments based on scriptural (Qur'an and Hadith) and rational reasoning. Those supporting religious freedom often cite verses like "There is no compulsion in religion," while opponents refer to war-related verses. It is generally agreed among Muslims that Qur'anic verses do not contradict each other. Based on this fact, the author is interested in examining Abdullah al-Harari's views on the verses related to the absence of compulsion in religion. Al-Harari, being a contemporary scholar staunch in adhering to the creed of Ahlussunnah Wal Jama'ah, has a strong focus on creed studies. Using the library research method, the researcher addresses two main problem formulations: (1) How does al-Harari understand the verses indicating the absence of compulsion in religion? (2) How does al-Harari reconcile these verses with the war-related verses? To answer these questions, the researcher examines al-Harari's interpretations in his works and those of his students, comparing them with the interpretations of other scholars in their exegesis works. This study concludes that al-Harari, following the interpretations of previous scholars, asserts that the belief in religious freedom is incorrect. The verses indicating the absence of compulsion in religion are understood as abrogated or that there is no compulsion against dhimmi (non-Muslim subjects) or against the hearts of unbelievers to enter Islam.